2014
DOI: 10.1021/jp408001t
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Water Molecule with Au(111) and Au(110) Surfaces under the Influence of an External Electric Field

Abstract: The interaction of water monomers with a gold surface is investigated using density functional theory (DFT) to develop a better understanding of the response of a water molecule to an imposed electric field at the surface. Two gold surface orientations, Au(111) and Au(110), are studied. Multiple unique stable adsorption positions of water molecules are identified for each surface orientation, and the results are validated against existing theoretical and experimental data. The values of the adsorption energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
13
36
1
Order By: Relevance
“…The rotation of H 2 O also shows that it is asymmetric with respect to the direction of the electric fieldit is more sensitive to a negative electric field. The asymmetry and greater rotation for a negative electric field agrees with the previously observed pattern for a water molecule adsorbed on gold 9 and copper 32 electrodes.…”
Section: Impact Of An External Electric Fieldsupporting
confidence: 90%
See 3 more Smart Citations
“…The rotation of H 2 O also shows that it is asymmetric with respect to the direction of the electric fieldit is more sensitive to a negative electric field. The asymmetry and greater rotation for a negative electric field agrees with the previously observed pattern for a water molecule adsorbed on gold 9 and copper 32 electrodes.…”
Section: Impact Of An External Electric Fieldsupporting
confidence: 90%
“…2 that the lone-pair orbitals display the most significant interaction with the 3d orbitals of the surface Cu atoms and also the most change (e.g., peak PDOS value, energy shifting and broadening) upon adsorption compared to other states at lower energies. This reveals that the Cu-χ interaction is the strongest interaction for both H 2 O and H 2 S. The stronger Cu-χ interaction is in agreement with the prediction that a small α value corresponds to a strong interaction between χ and the electrode [8][9][10]38 . Additionally, the PDOS change of the lone-pair orbitals is slightly greater for H 2 S, suggesting that the Cu-χ interaction is stronger for H 2 S than for H 2 O.…”
Section: Adsorption Without An Electric Fieldsupporting
confidence: 88%
See 2 more Smart Citations
“…More recently, calculations have shown that strong external electric fields perpendicular to the surface and of the same order of magnitude (1 V/nm), as used in this study, have the potential to push or pull an entire layer of water molecules adsorbed on Au by as much as 0.5 Å [15]. It has been suggested that such effects can be enhanced at protrusions in the surface, such as step sites, where the electric fields can be enhanced by as much as a factor of 5 [16].…”
mentioning
confidence: 80%